1996
DOI: 10.1128/iai.64.4.1321-1327.1996
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of lipopolysaccharide-responsive and -hyporesponsive ItyS Mice to infection with rough mutants of Salmonella typhimurium

Abstract: The R5 (chemotype Rb) but not the R10 (chemotype Rd) mutant of murine pathogen Salmonella typhimurium 395MS was extremely virulent in intraperitoneal infections of C57BL/10ScCr mice carrying the ity s and lps d alleles. C57BL/6J (ity s lps n) and C3H/HeJ (ity r lps d) mice showed a much higher resistance to the R5 mutant. Further studies were performed with peritoneal macrophages in vitro in order to elucidate susceptibility in lipopolysaccharide (LPS)-hyporesponsive mice carrying Ity s. The intracellular kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, deep rough mutants of Gram-negative bacteria in general are more sensitive to biological killing (39, 40). This fact should be taken into consideration in interpreting the data from the gentamicin survival assay of KIM10-Δ ail -Core − and CS2429 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, deep rough mutants of Gram-negative bacteria in general are more sensitive to biological killing (39, 40). This fact should be taken into consideration in interpreting the data from the gentamicin survival assay of KIM10-Δ ail -Core − and CS2429 (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The C3H/HeJ (Lpsd) mice showed endotoxin levels close to those of the other Lpsd group, suggesting that LPS clearance by the mononuclear phagocytic system was less effective, i.e., not having been activated. The capacity of Gram-negative bacteria to activate monocytic cells is diminished in Lpsd mice, which may partly reduce the clearance capacity (17,30,39). Therefore the endotoxin levels found in serum may be associated with the LPS susceptibility and the effectiveness with which invading bacteria are phagocytosed and killed in the presence of a ruptured mucosal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…A single gene, Lps, on mouse chromosome 4 regulates the responsiveness of the host to the lipid A part of the LPS molecule (5,23,40). The Lps gene locus profoundly influences the natural resistance of mice to a number of pathogenic organisms (17,24,35,41). Svanborg-Ed& et al showed that the Lps gene was important for the host resistance at mucosal sites (35).…”
mentioning
confidence: 99%
“…Both rough and smooth strains could block phagosome-lysosome fusion to enhance intracellular survival (5,25). However, during intracellular infection, rough strains were ultimately more susceptible to killing (41,51). When used in vaccination studies, smooth and rough strains can both induce protective cell-mediated immunity (45).…”
mentioning
confidence: 99%